Opaque Transparency: why California’s Supply Chain Transparency Act is Unenforceable - Greer, Benjamin Thomas (Oñati Socio-Legal Series, 2018)
Traffickers are dynamic, fluid operators; reacting well to consumer demand, under-regulated economic sectors, and easily adapting to exploit weaknesses in prevailing laws. Corporate globalization of storefronts and extensive manufacturing supply chains have contributed to human trafficking becoming the fastest growing criminal enterprise in the world. California’s legislative and social experiments are often models other governments look to for guidance. California is the first government to require businesses to disclose their anti-trafficking supply chain policies to their consumers. Under the California Transparency in Supply Chains Act of 2010 (CATSCA), large retailer sellers must conspicuously disclose on their web site their policies, if any, to detect and fight slave labor within their supply chain. This article explores the requirements of the CATSCA and will examine the legal effectiveness of the California transparency framework.